(3JGQjN GdQSd hGdedhcs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s ((3bQjI HXGgQ eOjfI gePGf s)
(3ChdgG (B:s
(3JHJOF ef SfI (B205(3g` , Hbhdg (B: (3PcQ GdNHQ YeG cGf ai gPg GdSfI ef GdCNHGQ efgG hdGjI GdeCehf PcQ GdNHQ Yf SHH Jhdjg Pdc (B: (3hcGf SHH Jhdjg EjGg NQGSGf s
(3BNQgG (B:s
(3JfJgi HBNQ CMOGK SfI (B247(3g` , Hbhdg hajgG hdi GdefJUQ CHG YeQI CMeO Hf SYjO ehdi Hfi gGTe HYO GdHjYI dg Hjhe GdeXGde hai gPg GdSfI CNQL GdefJUQ Ydi Hf GdeYJUe ef SQ ef QCi Edi HZOGO hML HGdfGS ajgG eMeO (B( (3GfJgi GdLRA (B) s
(3HgG JQbjY hJbWjYs
(3ai GdeYgO fSNJGf CNQjGf HQbe (B955 (3JGQjN hbO CKHJfG gfG GdYfhGf GdhGQO ai GdfSNJjf GdeagQSJjfs
(3hUfYfG EMdGdGJ ddQhGjGJ GdCNQis
(3cJHJ Hbde eged GdfbW CMjGfkG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
Keywords: (3GdJGQjNs